Sosialisasi, Pelatihan, dan Pendampingan OpenSID sebagai Upaya Digitalisasi Administrasi Kependudukan di Kelurahan Pematang Gubernur - Widya Ariyanti; Desvianti Desvianti; Davi Gunawan; Galang Januar Pratama; Caroline Anggun Prycillia Sitanggang; Gunawan Gunawan; RG Guntur Alam (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of information technology has significantly transformed government administration, enhancing public service efficiency and effectiveness. However, many local government offices still manage population administration manually, leading to delays and data inaccuracies. This community service activity aims to enhance the capacity of Pematang Gubernur Village staff in managing digital-based population administration through the implementation of OpenSID. A qualitative approach was used, consisting of several stages: preparation, socialization, training, mentoring, and evaluation. The results demonstrated that OpenSID facilitated the digitalization of population data, improving the staff's ability to manage administrative services. During the mentoring process, the staff learned to use the system for daily tasks such as managing population data and issuing administrative letters more efficiently. As a result, the village staff were able to deliver faster and more accurate services. This initiative marks the beginning of digital transformation in population administration at the village level, contributing to a more streamlined and effective service delivery system. Overall, the activity not only improved administrative efficiency but also empowered the village staff with the skills necessary for future digital advancements.